Une géopoétique : du récit de voyage à Canaima, de Rómulo Gallegos - François Delprat (Caravelle)
The reflection about links which join the travel story with the novel as life story, memory with project, discovery and its part of dream with knowledge, and art with real experience has lead Kenneth White to elaborate his concept of « geopoetics ». In his essay he applies it to the trip across time and space undertaken by the main characters of Canaima (1934), Rómulo Gallegos’ novel. He follows the steps of the novel’s genesis, to show how Gallego profits from facts found out in the Orinoco’s travellers’ stories, sometimes directly quoted by him : Sir Walter Raleigh, Alexander von Humboldt, Elysée Reclus, Jean Chaffanjon. The trip upstream looking for the sources of the great river and the voyage following the flow of its waters downstream becomes, through the novel, a return to the powers of the universe and a turbulent poetry of action in the flow of time.